Organizational Stress and Employee Productivity in Nepalese Commercial Banks: The Mediating Role of Employee Welfare - Bhandari, Dilli Ram; Subedi, Dhruba Prasad (International Journal of Social Sciences and Management, 2024)
Workplace stress refers to the physical and emotional strain caused by work-related pressures, which can negatively impact employee well-being and productivity. Employee welfare initiatives help to manage workplace stress by providing support systems and resources that promote well-being of the employees and leads to increase employee productivity and job satisfaction. This study aims to investigate how employee welfare impacts the relationship between organizational stress and employee productivity in Nepalese commercial banks. To accomplish this objective, data were collected from 312 respondents using a structured questionnaire, which was distributed via a convenience sampling method. The participants consisted of employees at managerial, officer and assistant level employees from various commercial banks. Data analysis was conducted using Process Macro 4, applying a 95% confidence interval and 5,000 bootstrapping samples. The findings reveal that employee welfare serves as a fully mediator in the relationship between organizational stress and employee productivity. This study demonstrates that organizations that are investing in employee welfare programs foster a healthier and more supportive work environment, contribute to reducing organizational stress, leading to improved performance and workplace morale. JEL Classification: J81, J24, J28 Int. J. Soc. Sc. Manage. Vol. 11, Issue-4: 119-125.